Lean Supply Chain Practices and the Performance of Kassmatt Supermarkets Limited - Wainaina, Mary; Odari, Sammy (International Journal of Supply Chain Management, 2023)
Purpose: The purpose of this study was to assess the influence of lean supply chain practices on the performance of Kassmatt Supermarket Limited. Methodology: A descriptive research design was used for the investigation. The study targeted 180 employees from Kassmatt supermarket limited. The sample size of the study was 124 respondents. The researcher utilized self-administered questionnaires to collect primary data with the aid of the drop and pick method. The pilot study utilized 10 percent of the actual sample size, which was equal to 12 participants. The data obtained from the questionnaires was analyzed using the statistical package for social sciences (SPSS) version 28. The study employed percentages, frequencies, means and standard deviations to analyze descriptive research. Inferential analysis was also done. Tables were used to present findings. Finally, multiple regression model was fitted into the study. Results: The findings revealed a positive significant relationship between lean supply chain practices in the elements of demand management, process standardization, lean customer practice, lean transport [predictor variables] and performance of Kassmatt Supermarkets Ltd. The study concluded that Kassmatt had implemented the aforementioned lean supply chain practices with the aim of improving its firm performance. Unique Contribution to Theory, Practice and Policy: The study enhances our understanding of lean supply chain methods and company performance. The study validated and extended supply chain management and performance theories by evaluating lean approaches in retail. The study's finding of additional variables that may affect lean practices and performance led to new suggestions. The study informed managers and practitioners about lean supply chain benefits. The study helped Kassmatt Supermarkets Limited and other merchants improve their supply chain management and operations. Supply chain management innovation and development may help organizations stay competitive in the rapidly changing business environment, according to the paper. The study informed policymakers and regulators on how lean supply chain methods may affect retail sector efficiency. Lean methods improve consumer satisfaction, waste reduction, and efficiency, which can inform retail supply chain excellence policies. The research also stressed the need of regulations encouraging industry-wide cooperation and knowledge sharing, which can increase innovation and efficiency.